2012
DOI: 10.1186/1472-6882-12-73
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a traditional Chinese medicine syndrome-specific outcome measure: the Kidney Deficiency Syndrome questionnaire (KDSQ)

Abstract: Background Development of Traditional Chinese Medicine (TCM) syndrome-specific outcome measures is needed for the evaluation of TCM syndrome-specific therapies. We constructed a Kidney Deficiency Syndrome Questionnaire (KDSQ) for the evaluation of the common TCM syndromes Kidney-Yin Deficiency Syndrome (KDS-Yin) and Kidney-Yang Deficiency Syndrome (KDS-Yang) in middle-aged women with menopausal symptoms. Methods KDS-Yin and KDS-Yang were traditionally defined by expert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…In our results, the constitution of yang-xu was significantly correlated with bladder problems, muscle/joint problems, depressive mood, and heart discomfort in the menopausal symptoms. These symptoms were similar to the 4 factors revealed by Chen et al [27] as the kidney-yang deficiency syndrome which included kidney-qi deficiency, deficiency cold, impaired kidney orifices, and abnormal urine excretion. We only focus on the main menopausal symptoms of menopausal women in our study to give a more simplified constitution differentiation We can infer that these symptoms of yang-xu constitution are predominate in postmenopausal women.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In our results, the constitution of yang-xu was significantly correlated with bladder problems, muscle/joint problems, depressive mood, and heart discomfort in the menopausal symptoms. These symptoms were similar to the 4 factors revealed by Chen et al [27] as the kidney-yang deficiency syndrome which included kidney-qi deficiency, deficiency cold, impaired kidney orifices, and abnormal urine excretion. We only focus on the main menopausal symptoms of menopausal women in our study to give a more simplified constitution differentiation We can infer that these symptoms of yang-xu constitution are predominate in postmenopausal women.…”
Section: Discussionsupporting
confidence: 60%
“…For example, German women suffer more from kidney yang deficiency, whereas Chinese women suffer more from kidney yin deficiency syndrome [33]. Chen et al [27] further constructed models to test and validate the premise that the menopausal syndrome could be either kidney yin and kidney yang. Borud et al [34] performed an Acuflash study to evaluate the effect of TCM acupuncture on postmenopausal vasomotor symptoms, and found that 50% of the participants were diagnosed with kidney yin xu as their primary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Its symptoms include pain in the back or the knees, forgetfulness, tidal fever, night sweating, dizziness, tinnitus, insomnia, thirst at night, etc. [11]. In the Orient, Yukmijihwang decoction has been used typically for more than a thousand years for the treat ment of this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of kidney-yin deficiency Zheng fall into the category of "heat". These include sore waist and knees, skelasthenia, vertigo and tinnitus, insomnia and dreaminess, postcoital protrusion or impotence or nocturnal emission in man, hypomenorrhea or menostasis even uterine bleeding in woman, emaciation, feverish night sweating, burning sensation of five centers, dry pharynx and red cheeks, juvenile leukotrichia, somniloquence and bruxism, frequency of micturition, dark yellow urine, dry stool, red tongue with sparse saliva, rapid and thready pulse [33,35,36].…”
Section: Differentiation From Liver Cancer With Other Zheng Classificmentioning
confidence: 99%